2005
DOI: 10.1111/j.1469-7580.2005.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐plastinated vs. celloidin‐embedded large serial sections in video, analog and digital photographic on‐screen reproduction: a preliminary step to exact virtual 3D modelling, exemplified in the normal midface and cleft‐lip and palate

Abstract: This study analyses tissue-plastinated vs. celloidin-embedded large serial sections, their inherent artefacts and aptitude with common video, analog or digital photographic on-screen reproduction. Subsequent virtual 3D microanatomical reconstruction will increase our knowledge of normal and pathological microanatomy for cleft-lip-palate (clp) reconstructive surgery. Of 18 fetal (six clp, 12 control) specimens, six randomized specimens (two clp) were BiodurE12 -plastinated, sawn, burnished 90 µ m thick transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Nor were external fiducial markers used (Brä ndle, 1989;Hara et al, 1989;McLean and Prothero, 1991;Streicher et al, 1997) for realignment and deformation calculation. Preliminary artifact assessment (Landes et al, 2005) showed isolated structures to be differently deformed than the whole anatomic conformation. Therefore, external fiducials yield merely approximate deformation information because each tissue is deformed with different elasticity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nor were external fiducial markers used (Brä ndle, 1989;Hara et al, 1989;McLean and Prothero, 1991;Streicher et al, 1997) for realignment and deformation calculation. Preliminary artifact assessment (Landes et al, 2005) showed isolated structures to be differently deformed than the whole anatomic conformation. Therefore, external fiducials yield merely approximate deformation information because each tissue is deformed with different elasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Both techniques were used to compare detail recognition and artifact correction not merely to apply one embedding and staining method but to be able to evaluate software algorithms in different situations. Because detail was lost with the plastination approach (Landes et al, 2005), the celloidin-hematoxylineosin method was relied on for the present study. The transverse cutting plane was preferred because it followed the mainly anterioposterior course of the soft palate muscles.…”
Section: Discussionmentioning
confidence: 99%
“…To provide a suitable finite element conformal tetrahedral mesh on the basis of images of histological serial sections annotated with polygonal segments (Landes et al, 2005) a level set approach is used to construct an implicit surface on a rectilinear grid (Zhao et al, 2001). The surface is used to guide an octree subdivision process and is determined by time evolving an initial guess through a physically motivated convection model that is described by the following level set equation:…”
Section: Three-dimensional Reconstruction Of a Striated Skeletal Musclementioning
confidence: 99%
“…All cases were classified post mortem to be beyond Carnegie stage 20. Steps of tissue preparation have been published elsewhere (Landes et al, 2005). Three basic steps were designed to constitute the aforementioned systems biological approach: mesh generation, computation of contraction directions and last not least simulation of contracting striated muscle activity (see Fig.…”
Section: Methodsmentioning
confidence: 99%